2018
DOI: 10.1039/c7nj03887a
|View full text |Cite
|
Sign up to set email alerts
|

A selective colorimetric sensing strategy for cysteine based on an indicator-displacement mechanism

Abstract: Rapid determination of cysteine in aqueous solution is important for the diagnosis and treatment of some diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…L-cysteine is a biologically significant thiol, the discrepancies in whose levels can lead to decolorization of hair, skin and lung diseases, psoriasis, etc. [174][175][176] A recent study showed the synthesis of a nanocomposite of MoS 2 quantum dots and Ag NPs, which were employed for a colorimetric assay of cysteine [101] (Figure 8c). However, they reported a LOD of 0.82 µM, which was much higher than another nanocomposite-based cysteine detection using DNA functionalized Ag-Pt nanoclusters.…”
Section: Detection Of Natural Biomarkersmentioning
confidence: 99%
“…L-cysteine is a biologically significant thiol, the discrepancies in whose levels can lead to decolorization of hair, skin and lung diseases, psoriasis, etc. [174][175][176] A recent study showed the synthesis of a nanocomposite of MoS 2 quantum dots and Ag NPs, which were employed for a colorimetric assay of cysteine [101] (Figure 8c). However, they reported a LOD of 0.82 µM, which was much higher than another nanocomposite-based cysteine detection using DNA functionalized Ag-Pt nanoclusters.…”
Section: Detection Of Natural Biomarkersmentioning
confidence: 99%
“…39,48 The detection of L-cysteine is important as its deficiency can cause anomalous cell growth, skin lesions, lethargy, hair depigmentation, liver damage, and malabsorption syndrome, 39 while high levels of L-cysteine can be neurotoxic and cause cardiovascular diseases. 49 Our previous work employing other NZs for L-cysteine sensing showed that the catalytic activity of the NZs was lost after their interaction with L-cysteine. In-depth analysis revealed that the mechanism of the interaction of L-cysteine with the NZ can be different depending on the NZ used.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of catalysis, enzyme-mimicking catalytic nanoparticles or nanozymes (NZs) have gained remarkable interest with wide-spread applicability across sensing, bioimaging, environmental clean-up, and pro-drug therapy. Given that the composition of the nanoparticle can influence the catalytic efficiency, a suite of nanoparticles including metals, metal oxides, metal sulfides, etc ., have been reported for wide-ranging enzyme-mimic activities. , Of these, metal sulfides have been suggested to be superior catalyst candidates as the M–S bonds are weaker than the M–O bonds in the corresponding metal oxides . Further, NZ-based sensors have gained attention in analytical science as they allow visual detection of the sensing event. , Such sensors have been used for the detection of several chemical and biological molecules including l -cysteine, a thiol containing semi-essential amino acid found in a number of proteins. , The detection of l -cysteine is important as its deficiency can cause anomalous cell growth, skin lesions, lethargy, hair depigmentation, liver damage, and malabsorption syndrome, while high levels of l -cysteine can be neurotoxic and cause cardiovascular diseases …”
Section: Introductionmentioning
confidence: 99%
“…This method relies on the naked eye to read the concentration of various biomolecules through different intensities of color, allowing the field detection of the analyte without any complex instruments. 24–27 It is a mature and economical method for the rapid and intuitive determination of various biomolecules at trace levels in real samples and has made remarkable progress.…”
Section: Introductionmentioning
confidence: 99%